Primary extranodal soft tissue Lennert lymphoma (lymphoepithelioid variant of peripheral T-cell lymphoma, unspecified): a case report and review of the literature - Ying Yin; Huaipu Liu; Minghua Luo; Guangyin Yu; Weihua Yin; Ping Li (BMC, 2023)
Abstract Lennert lymphoma (LeL) is a rare variant of peripheral T-cell lymphoma, not otherwise specified (PTCL/NOS) that is rich in epithelioid histiocytes. LeL may pose great diagnostic and therapeutic challenges to the pathologist and clinician. Primary extranodal soft tissue LeL is even rarer and has not been reported. Herein, we report a case of LeL arising from soft tissue. A 65-year-old male presented for evaluation of a painless mass in the subcutaneous soft tissue of the left forehead. There was no invasion of the bone and no ulceration on the surface of the skin. The surrounding skin was erythematous and swollen. Grossly, the tumor was gray-red and 30 mm × 20 mm × 10 mm in size. Microscopically, the demarcation between the lesion and surrounding tissues was unclear without a capsule. The tumor invaded the surrounding striated muscle and adipose tissue. The tumor had a diffuse proliferation of small-sized atypical lymphocytes and numerous large clusters of epithelioid histiocytes. Plasma cells, eosinophils, and Hodgkin-Reed-Sternberg (HRS) cells were not identified. Rare multinucleated histiocytes were noted, and well-formed granulomas were not present. Rare mitotic figures were noted, but no necrosis. The immunophenotypic features in this case were as follows: CD2+/CD3+/CD5low+/CD7+/CD4low+/ CD8+/CD30−/CD56− in neoplastic lymphocytes; CD163+/CD31+/CK(pan)− in epithelioid histiocytes; and CD20−/CD30−/TdT−/CD5−/ALK−/S-100−/CD1α−/CD21 + 23−/SSTR2− in neoplastic lymphocytes and epithelioid histiocytes. Epstein-Barr virus (EBV)-encoded RNA in situ hybridization (EBER-ISH) was negative. The Ki-67 index was elevated to 60%. PCR showed a polyclonal pattern for IgH and a monoclonal TCR γ-chain rearrangement. The final diagnosis was PTCL/NOS, lymphoepithelioid cell variant (LeL), which arose from soft tissue and had a rare double-positive CD4low+/CD8+ immunophenotype. The patient received four cycles of cyclophosphamide, doxorubicin liposomes, vincristine, and prednisone tablets (CHOP) and was followed for 20 months. Overall treatment efficacy was achieved without lymphadenopathy, and no other discomfort or illnesses were reported.